Health policies on dialysis modality selection: a nationwide population cohort study. Issue 1 (11th January 2017) - Lin, Yi-Chun; Lin, Yen-Chung; Kao, Chih-Chin; Chen, Hsi-Hsien; Hsu, Chih-Cheng; Wu, Mai-Szu
Abstract : Objectives: In Taiwan, peritoneal dialysis (PD) and haemodialysis are fully accessible to patients with end-stage renal disease. However, the usage of PD is considered low in Taiwan. Since 2005, 4 major policies have been implemented by Taiwan's Ministry of Health and Welfare, namely a multidisciplinary predialysis care programme and usage increasing the PD incidence as a key performance indicator (KPI) for hospital accreditation, both of which were implemented in 2006; reimbursement of the glucose-free dialysate, icodextrin that was implemented in 2007; and insurance reimbursement for renting automated PD machines that was implemented in 2008. The aim of this study was to analyse the associations between the PD promotional policies and the actual PD selection rates. Setting: We analysed data within the Taiwan Renal Registry Data System from 2006 to 2013, focusing on the PD incidence in relation to the timings of the 4 PD promotional policies; then we stratified the results according to age, sex and the presence of diabetes mellitus. Participants: From 2006 to 2013, 115 565 patients were enrolled in this study. The mean (SD) age of patients on PD was 54.6 (15.7) years. Results: During the time frame in which the 4 PD promotional policies were implemented, the PD incidence increased from 12.8% in 2006 to 15.1% in 2009. The PD incidence started to decline in 2010 (13.8%) when the hospital accreditation policy was repealed. The 3 remaining policies were weakly associated with the PD incidence. The observational analysis determined that the patients' ages, sexes and diabetes mellitus incidence rates were relatively stable from 2006 to 2013. Conclusions: Of the 4 health policies intended to promote PD usage, using increasing the PD incidence as a KPI for hospital accreditation had the strongest association with the PD incidence.